ANALISIS KUALITAS LULUSAN BERDASARKAN TINGKAT KEPUASAN PENGGUNA LULUSAN - Ira Setyaningsih; Muchammad Abrori (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2013)
In education, the students are the products to be input and the output are graduates. Users of graduates are consumers who need to know the level of satisfaction to provide a self-evaluation in improving the institutions. It is also stated in the accreditation forms BAN PT. However, a grain questions that sought to know is very little. The research was conducted at a university in Yogyakarta. Research trying to describe in detail the attributes of quality of graduates based on the user satisfaction level graduates. Object of study is alumni and also alumni users. The study was conducted during the months of August to November 2012. Attributes used are Communication Skills, Organizational Skills, Leadership, Logic, Effort, Ethics, Group and Other Skills. Other attributes are attributes about the ability of areas of expertise. From the results obtained, the attributes that need attention are Organizational Skills and Leadership with the highest gap -0.82. Overall, users of alumni do not feel satisfied, because all negative attributes.